A Case of Congenital Heart Defect for First-Year Medical Students - Team-Based Learning Format - Maria Sheakley; Julie Baumberger; Charles Seidel; Liris Benjamin; Charlotte Rhodes (Association of American Medical Colleges, 2009)
Abstract Introduction This resource is a team-based learning module on congenital heart defects designed for first-year medical students. By using this resource, students will be able to understand and appreciate the value of a systems-based approach to exploring and discussing information with a patient who has a congenital heart defect. Methods Team-based learning cases utilize a specific written format and method of facilitating to produce very effective small-group and class discussions. There is a detailed description of this process in the facilitator's version of the module. Students should have an understanding of basic cardiovascular diagnostic tools such as an echocardiogram, electrocardiogram, wedge pressure, and cardiac catheterization. They should also be able to recognize how to utilize these diagnostic tools to diagnose a basic cardiovascular pathology. Results The purpose of this module was to introduce clinical materials to first-year medical students to stimulate group discussion and critical thinking. This case was very effective in achieving all of these goals, and the student feedback was overall positive. The case was particularly successful in helping students to "see the big picture" and aided them in their overall understanding of cardiovascular physiology as a whole. Discussion In our experience, the students found this case to be interesting and a positive learning experience. They liked interpreting the diagnostic tests. The discussion was excellent, particularly for the second question of the clinical case which was difficult enough to stimulate a lot of discussion as to why some of the answer choices were incorrect.